2016
DOI: 10.1007/s13197-016-2365-y
|View full text |Cite
|
Sign up to set email alerts
|

Stable nisin food-grade electrospun fibers

Abstract: Most of antimicrobial peptides interact with food components decreasing their activity, which limit their successful incorporation into packaging material, functional foods and edible films. The aim of this work was to develop a nisin carrier. Nanofibers of amaranth protein and pullulan (50:50) loaded with nisin were obtained by electrospinning. The nanofibers morphology was determined by scanning electron microscopy and fluorescent microscopy. The molecular interactions were characterized by infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Nisin is used in more than 48 countries and approved by the USFDA. Nisin can inhibit the growth of a broad spectrum of Gram-positive microorganisms, such as Listeria monocytogenes [51,52] and prevent spore germination [53]. Nisin has both positive charges and hydrophobic groups.…”
Section: Natural Antimicrobial Agent and Their Application In Foodmentioning
confidence: 99%
“…Nisin is used in more than 48 countries and approved by the USFDA. Nisin can inhibit the growth of a broad spectrum of Gram-positive microorganisms, such as Listeria monocytogenes [51,52] and prevent spore germination [53]. Nisin has both positive charges and hydrophobic groups.…”
Section: Natural Antimicrobial Agent and Their Application In Foodmentioning
confidence: 99%
“…Nanostructure materials have been studied for the protection of AMPs antimicrobial activity, for example, nanoparticles, nanoliposomes, and nanofibers (Mahdavi, Mohammad, & Nouri, 2019;Soto et al, 2016;Wu et al, 2017). bial and antioxidant activity, which also showed enhanced stability of nisin and curcumin (Luo et al, 2020).…”
Section: Active Packaging and Nanotechnologiesmentioning
confidence: 99%
“…ESF‐AMP systems have also used organic co‐polymer combinations to produce fibers . Produced ESFs of amaranth protein and pullulan together with the AMP nisin for food preservation instead of wound healing have been made.…”
Section: Antimicrobial Peptide‐based Electrospun Fibersmentioning
confidence: 99%
“…A total of 13 different AMPs have been utilized with studies being reported in 18 publications as of 2019 ( Table 4 ). The most common AMP studied to date is nisin . Nisin ( Figure 5 ) is one of the most well‐known bactericidins and is the only american food and drug administration (FDA) food grade approved antimicrobial, thus making it an attractive choice for exploratory studies in combining AMPs with other technologies such as electrospinning.…”
Section: Antimicrobial Peptide‐based Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation